Proof of the Accuracy of Calculation of Trigonometric Formulas for Spherical Triangles with Magnetic Declination Correction at Istiwa A'zam in Determining the Direction of the Qibla - Caniago, Abdi Samra; Athar, Gadis Arniyati (International Journal on Advanced Science, Education, and Religion, 2024)
This study departs from Arbisora's research which shows that there is a difference in the direction of the Qibla of the Al-Mashun Grand Mosque in Medan which is determined by the hisab method and the rashdul Qibla method. The researcher's temporary assumption is that this is because the hisab does not use magnetic declination. This study aims to prove the accuracy of the Qibla direction using the spherical triangle trigonometric hisab method with magnetic declination correction and the istiwa a'zam event. The research is field research, which was carried out at the Al-Mashun Grand Mosque in Medan City on July 15, 2024 which coincided with the istiwa a'zam event. The coordinate data of the Al-Mashun Grand Mosque in Medan was obtained from Garmin GPS 60, which is 98°41' 4.14" East Longitude and 3ᴼ 34' 30.79" North Latitude. For the coordinate data of the Kaaba, the latest data from Ahmad Izzuddin was used, as per the results of the study in 2007, namely 39ᴼ 49' 34.56" East Longitude and 21ᴼ 25' 21.17" North Latitude. The results of the study revealed that the calculation results of the spherical triangle trigonometry method with magnetic declination correction for the direction of the Qibla of the Al-Mashun Grand Mosque in Medan, namely the West to North Direction value = 23ᴼ 13' 52.2", the North to West Direction value = 66ᴼ 46' 7.8", and the azimuth value = 293ᴼ 13' 52.2". While the calculation results did not use magnetic declination correction, the azimuth value was 292ᴼ 46’ 26.95”. The results of field research on July 15, 2024 at 16:26 WIB during the istiwa a’zam event found that the Qibla Azimuth of the Al-Mashun Grand Mosque showed 293ᴼ the same as the rashdul Qibla from Arbisora ​​293ᴼ 20’ 49.18”. This proves that the hisab method using the magnetic declination correction method is more accurate.